2013
DOI: 10.1016/j.jinsphys.2012.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The Bunsen–Roscoe reciprocity law in ultraviolet-B-induced mortality of the two-spotted spider mite Tetranychus urticae

Abstract: To determine whether the Bunsen-Roscoe reciprocity law (i.e., the extent of photochemical effects is determined by cumulative irradiance) is applicable to ultraviolet-B (UVB) damage in the twospotted spider mite Tetranychus urticae, egg hatchability and survival of individuals were assessed after irradiation with a UVB lamp using various combinations of intensity and time length. A positive linear correlation between probit mortality and cumulative UVB irradiance was detected in eggs, larvae, teleiochrysalis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 27 publications
(34 reference statements)
3
36
0
1
Order By: Relevance
“…Artificial UV-B irradiation was reported to reduce the incidence of fungal diseases, such as strawberry powdery mildew (Kanto et al, 2009(Kanto et al, , 2014, rose powdery mildew (Kobayashi et al, 2013), and eggplant leaf mold caused by Mycovellosiella nattrassii (Oka et al, 2011). Moreover, it was reported that UV-B irradiation hindered the survival and reproduction of the herbivorous spider mite Tetranychus urticae (Murata and Osakabe, 2013;Ohtsuka and Osakabe, 2009). The mortalities of adult females, larvae, and eggs of T. urticae were proportional to the cumulative UV-B irradiance to which they were exposed (Murata and Osakabe, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial UV-B irradiation was reported to reduce the incidence of fungal diseases, such as strawberry powdery mildew (Kanto et al, 2009(Kanto et al, , 2014, rose powdery mildew (Kobayashi et al, 2013), and eggplant leaf mold caused by Mycovellosiella nattrassii (Oka et al, 2011). Moreover, it was reported that UV-B irradiation hindered the survival and reproduction of the herbivorous spider mite Tetranychus urticae (Murata and Osakabe, 2013;Ohtsuka and Osakabe, 2009). The mortalities of adult females, larvae, and eggs of T. urticae were proportional to the cumulative UV-B irradiance to which they were exposed (Murata and Osakabe, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was reported that UV-B irradiation hindered the survival and reproduction of the herbivorous spider mite Tetranychus urticae (Murata and Osakabe, 2013;Ohtsuka and Osakabe, 2009). The mortalities of adult females, larvae, and eggs of T. urticae were proportional to the cumulative UV-B irradiance to which they were exposed (Murata and Osakabe, 2013). Greenhouse experiments revealed an excellent controlling effect of UV-B irradiation on T. urticae populations on strawberries (Tanaka et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Biological measures using commercialized natural enemies have been put to practical use (Yang et al 2014), whereas physical measures against spider mites have remained unexploited (Suzuki 2012). Although the use of ultraviolet radiation has recently received broad attention due to its miticidal and repellent effects against spider mites (Ohtsuka and Osakabe 2009;Suzuki et al , 2013Suzuki et al , 2014Sakai and Osakabe 2010;Murata and Osakabe 2014), it may be difficult to apply practically because of the uneven irradiation caused by leaf self-shading. Here, we focused on modification of the atmosphere, which is expected to produce relatively uniform effects throughout the plant because of the rapid diffusion that occurs with gases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar work was carried out with Tetranychus urticae, but this time aiming to assess the effect of exposure to UV rays. Brief UV exposure periods lead to larvae death and unviable eggs (28). NavasPanadero (14) evaluated the photosynthetically active radiation and its effect on the number of larvae of ticks found in pastures with different silvopastoral arrangements and found no difference between the silvopastoral and more conventional arrangements.…”
Section: (B) Microplusmentioning
confidence: 99%
“…This could lead to a decrease of larvae and viable egg numbers in the pastures, thus obtenidos en individuos tratados con poco tiempo de exposición a los rayos UV fueron la muerte de larvas y la inviabilidad de los huevos (28). Navas (14) evaluó la radiación fotosintética activa y su efecto en el número de larvas de garrapatas que se encuentran en potreros con diferentes arreglos silvopastoriles y no encontró diferencias entre el arreglo silvopastoril y el no silvopastoril.…”
Section: (B) Microplusunclassified